Myomectomy at the time of Cesarean Section: A Prospective Multicentre Study (Journal of Current and Advance Medical Research, 2019)
Background: Myomectomy can be performed during cesarean section.Objective: The purpose of the present study was to assess the safety and efficacy of myomectomy during cesarean section.Methodology: The study design was a prospective multi-centre study done in three tertiary care hospitals Dhaka Medical Collage, BSMMU & private Hospital in Dhaka City. The subject were 65 pregnant women elective or emergency myomectomy during cesarean section. All cesarean section myomectomy were performed by consultants. Intra-operative and post-operative complications such as change in haematocrit, length of operation, blood loss were estimated. Length of hospital stay was also recorded.Results: 79 Fibroid of various sizes (2 to 6cm) were removed from 65 women. Fibroid were on the anterior uterine wall with most being sub serous and intra mural. Four patients had one unit of whole blood transfusion in post-operative period. No hysterectomy was done at the time of cesarean section. There was no significant change of haematocrit: incidence of post-operative fever and duration of operation. The mean duration of post-operative hospital study was 7.3±1.2 days, 5 patients subsequently became pregnant, were also underwent repeated cesarean section in the study period.Conclusion: In selected cases myomectomy during cesarean section does not appear to result in an increased risk of intrapartum or short-term post-partum morbidity if performed by an experienced practitioner. Cesarean myomectomy is a safe surgical options with no significant complications.Journal of Current and Advance Medical Research 2019;6(1):18-22